Global environmental agreements and international trade: Asymmetry of countries matters - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2014)
We investigate the formation of global climate agreements (= stable grand climate coalitions) in a model, in which climate policy takes the form of carbon emission taxation and fossil fuel and consumption goods are traded on world markets. We expand the model of Eichner and Pethig (2014) by considering countries that are identical within each of two groups but differ across groups with respect to climate damage or fossil fuel demand. Our numerical analysis suggests that climate damage asymmetry tends to discourage cooperation in the grand coalition. The effects of fuel-demand asymmetry depend on fossil fuel abundance. If fuel is very abundant, the grand coalition fails to be stable independent of the degree of fuel demand asymmetry. If fuel is sufficiently scarce, low degrees of fuel demand asymmetry discourage cooperation whereas higher degrees of asymmetry stabilize the grand coalition.
Keywords: C72; F02; Q50; Q58; 330; fuel demand; climate damage; international trade; asymmetry; stability; grand coalition